2019
DOI: 10.1021/acschemneuro.8b00605
|View full text |Cite|
|
Sign up to set email alerts
|

Neuroprotective Effect of Swertiamain on Cerebral Ischemia/Reperfusion Injury by Inducing the Nrf2 Protective Pathway

Abstract: Oxidative stress plays a vital role in the development of cerebral ischemic/reperfusion (I/R). Targeting oxidative stress is proposed to be an effective strategy to treat cerebral I/R injury. Gentiana macrophylla Pall is reported to have a potential protective effect against stroke. Swertiamarin (Swe), an active secoiridoid glycoside compound isolated from Gentiana macrophylla Pall, has been reported to possess antioxidative potential. This study is to explore whether Swe could prevent brain from I/R injury, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…in the present study, Pc12 cells that received oGd/r served as the cellular model, which has been used in numerous previous studies (24,25,34,35). consistent with the previous studies, the cell apoptotic rate, the inflammatory status and NO levels were increased following oGd/r induction, indicating that the cellular model was successfully established (36,37). in a previous study, the expression levels of mir-340-5p were rapidly decreased in the peripheral blood of patients who had suffered from an acute ischemic stroke, which indicated a potentially protective role for mir-340-5p in ischemic stroke (22).…”
Section: Discussionsupporting
confidence: 83%
“…in the present study, Pc12 cells that received oGd/r served as the cellular model, which has been used in numerous previous studies (24,25,34,35). consistent with the previous studies, the cell apoptotic rate, the inflammatory status and NO levels were increased following oGd/r induction, indicating that the cellular model was successfully established (36,37). in a previous study, the expression levels of mir-340-5p were rapidly decreased in the peripheral blood of patients who had suffered from an acute ischemic stroke, which indicated a potentially protective role for mir-340-5p in ischemic stroke (22).…”
Section: Discussionsupporting
confidence: 83%
“…The results obtained for catalposide are similar to those reported by Moon et al Catalpol, another glycosylated iridoid, showed a protective effect against oxidative stress induced by H 2 O 2 in a primary astrocyte culture 58 . Wang et al evaluated the Nrf2-mediated neuroprotective capacity of swertiamarin, a glycosylated secoiridoid, and reported increases in the levels of the antioxidant proteins NQO1 and HMOX-1 in addition to an increase in the Nrf2 protein at the nuclear level 59 . The only report of the protective effects of specioside was made by Asthana et al, in which the ability of the compound to modulate antioxidant enzymes such as CAT and SOD was evaluated in a Caenorhabditis elegans model 60 .…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained for catalposide are similar to those reported by Moon et al Catalpol, another glycosylated iridoid, showed a protective effect against oxidative stress induced by H 2 O 2 in a primary astrocyte culture 60 . Wang et al evaluated the Nrf2-mediated neuroprotective capacity of swertiamarin, a glycosylated secoiridoid, and reported increases in the levels of the antioxidant proteins NQO1 and HMOX-1 in addition to an increase in the Nrf2 protein at the nuclear level 61 . The only report of the protective effects of specioside was made by Asthana et al, in which the ability of the compound to modulate antioxidant enzymes such as CAT and SOD was evaluated in a Caenorhabditis elegans model 62 .…”
Section: Discussionmentioning
confidence: 99%